Fragmentation and biodiversity change in urban vegetation: A case study of tram lines - Winkler, Jan; Koda, Eugeniusz; Červenková, Jana; Napieraj, Krzysztof; Żółtowski, Mariusz; Jakimiuk, Aleksandra; Podlasek, Anna; Vaverková, Magdalena Daria (John Wiley & Sons, Inc., 2024)
This study explores the vegetation composition along various tram line sections in Bydgoszcz, Poland, with a focus on understanding the impact of usage, maintenance, and historical development on urban vegetation dynamics. This study addresses this knowledge gap by investigating how these factors influence plant species composition, leading to variations in the prevalence of native and non-native species. The aim of this study is to contribute to urban ecological knowledge and inform vegetation management strategies. The investigation centers on five tram line sites representing different usage and maintenance scenarios: Unused line, New line, Loop rec, Loop old, and Old line. Through phytocoenological relevés conducted in 2020 and 2021, we measured the plant taxa coverage. Detrended Correspondence Analysis (DCA) and Canonical Correspondence Analysis (CCA) revealed relationships between plant species and tram line sites. The results indicated the presence of 107 plant taxa, with graphical representations highlighting the prevalent species on each tram line section. Older sections showed a higher representation of non-native plant species, whereas new sections exhibited native species dominance. Moisture-indicative values suggest an affinity for soils with average moisture content. CCA provides insights into the relationships between plant taxa and site variants and offers valuable implications for urban vegetation management and conservation strategies. The novelty of this study lies in its holistic approach for understanding how multiple factors interact to shape urban vegetation. By illuminating urban ecological dynamics and informing decision-making processes, this study contributes to urban planning, ecology, and biodiversity conservation. Additionally, this study fills a knowledge gap by providing insights into the unique ecological dynamics and species composition of tram lines in urban environments. Unlike previous research in Central European countries focusing on planted vegetation, this study explored the spontaneous spread of plants and successional patterns along tram lines, enhancing our understanding of the environmental conditions created by tram lines that influence vegetation composition and development.
Keywords: biodiversity; native and non-native species; transportation; urban ecology; urban vegetationdynamics; vegetation management